Implicative and positive implicative filters of residuated lattices in multiset context. (4th July 2019) - Vimala, J.; Anusuya Ilamathi, VS.; Rajareega, S.
Abstract: In this paper, we introduce the concept of multiset implicative filter and multiset positive implicative filter of residuated lattice. Also, we discuss their characterizations and we show that M is a multiset implicative filter of X if and only if the quotient residuated lattice X/M is a Heyting algebra.